2013
DOI: 10.1017/s0950268813002033
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular epidemiology of Staphylococcus aureus in Swedish nursing homes – as revealed in the SHADES study

Abstract: SUMMARYKnowledge of carriage and population dynamics of Staphylococcus aureus is crucial for infection risk assessment and to reveal transmission patterns of strains. We report the prevalence and molecular epidemiology of S. aureus in elderly people (n = 290) living in nursing homes in three cities in the south of Sweden. The overall carriage prevalence rate was 48% when results from nares (31%) and throat (34%) samples were combined. Common spa types were equally distributed but a frequent type, t160, was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(74 reference statements)
1
13
1
1
Order By: Relevance
“…This differs from the study by Haslund et al demonstrating that S. aureus of the same spa type always colonize the anterior nares and hand of a patient [6]. Simultaneous colonization with S. aureus of different spa types and simultaneous colonization with susceptible and resistant strains has been documented previously [36,37]. In case of an infection with multiple types, antibiotic susceptibility testing of solely one colony could lead to the detection of a susceptible rather than a resistant strain and thereby antibiotic treatment failure.…”
Section: Discussioncontrasting
confidence: 80%
“…This differs from the study by Haslund et al demonstrating that S. aureus of the same spa type always colonize the anterior nares and hand of a patient [6]. Simultaneous colonization with S. aureus of different spa types and simultaneous colonization with susceptible and resistant strains has been documented previously [36,37]. In case of an infection with multiple types, antibiotic susceptibility testing of solely one colony could lead to the detection of a susceptible rather than a resistant strain and thereby antibiotic treatment failure.…”
Section: Discussioncontrasting
confidence: 80%
“…A significant association between HCWs and a specific spa type (t160) was identified in paper IV, which is in line with a previous study, which, however, identified an association between two other spa types, namely t012 and t015, and HCWs (Olsen et al 2013). t160 was also the most common spa type in nursing homes in the same geographical area as the studies in papers III and IV (Stark et al 2014). This adds to the indication already suggested, based on the high prevalence of the previously undetected t084 in the region, that some strains are more prone to transmission and are more successful colonizers.…”
Section: Spa Type Distribution and Cluster Analysis (Papers III And Iv)supporting
confidence: 89%
“…Of the 29 most commonly identified spa types (figure 2, paper IV), 12 were found in the largest spa CC (spa CC 015). This spa CC has previously been identified as the largest spa CC among elderly people living in nursing homes in southern Sweden (Stark et al 2014). Only two of the 29 most common spa types (t084, the most commonly identified spa type, and t085) were found in the second largest spa CC.…”
Section: Spa Type Distribution and Cluster Analysis (Papers III And Iv)mentioning
confidence: 62%
See 2 more Smart Citations